2024
DOI: 10.17645/mac.7836
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Sampling for Systematic Literature Reviews (STAMP Method): Ensuring Reproducibility and Replicability

Ayanda Rogge,
Luise Anter,
Deborah Kunze
et al.

Abstract: Systematic literature reviews (SLRs) are an effective way of mapping a research field and synthesizing research evidence. However, especially in communication research, SLRs often include diverse theories and methods, which come with a considerable downside in terms of reproducibility and replicability. As a response to this problem, the present article introduces the method of standardized sampling for systematic literature reviews (STAMP). The method is a structured, four-stage approach that is centered arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…A systematic literature review (SLR) is a suitable method for addressing the intended research objectives, as it enables the exploration of a broad, heterogeneous, and interdisciplinary research field in a reproducible and reliable way (Rogge et al, 2024). The methodological approach is based on the recommendations of Petticrew and Roberts (2006) and the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) checklist, as well as corresponding recommendations for systematic literature reviews (Page et al, 2021), and the STAMP method (Rogge et al, 2024). Two types of literature reviews-a scoping review and a theoretical review-were combined to connect the summarization of prior knowledge with further explanation building through a comprehensive search strategy (Paré et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic literature review (SLR) is a suitable method for addressing the intended research objectives, as it enables the exploration of a broad, heterogeneous, and interdisciplinary research field in a reproducible and reliable way (Rogge et al, 2024). The methodological approach is based on the recommendations of Petticrew and Roberts (2006) and the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) checklist, as well as corresponding recommendations for systematic literature reviews (Page et al, 2021), and the STAMP method (Rogge et al, 2024). Two types of literature reviews-a scoping review and a theoretical review-were combined to connect the summarization of prior knowledge with further explanation building through a comprehensive search strategy (Paré et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Neither Krippendorff 's alpha nor Cohen's kappa coefficients were optimal but they reached acceptable values after the second reliability test. Here, it has to be borne in mind that the homogeneity (e.g., a majority of the publications did not fulfill ABS criterion 2) and dichotomy (0/1) of most of the data may have been a problem for the usage of these coefficients (Rogge et al, 2024). During the reliability tests, it was observed that ABS criterion 2-the connection of destigmatization with media or communication-is hard to decide on, as media and communication are broad and diverse concepts.…”
Section: Abstract-based Screeningmentioning
confidence: 99%